Carbon Isotope Investigation of Freshwater Tufa Precipitation in Karst Streams of Bükk Mountains (Hungary) - Bódai, Barbara; Baráth, Balázs Áron; Gergely, Virág; Sóvágó, Dávid; Braun, Mihály; Futó, István; Kele, Sándor; Molnár, Mihály (Journal of Environmental Geography, 2023)
Recent freshwater tufa precipitation and its parent water were investigated at Szalajka valley, Sebesvíz and Dobrica Spring (Bükk Mts., Hungary). The aim of the study is to analyse the carbon isotope dynamics of freshwater tufa precipitated in karstic streams between the spring water and the first significant tufa barrage using field measurements, water chemistry, and carbon isotope analysis. A further aim was to examine the fossil tufa precipitations in recently active areas and their neighbourhood to determine their age using the 14C method. Based on the 3H content the water samples are relatively young (<10 y). To calibrate the calendar age of older tufas, dead carbon proportion (dcp) were determined in the recently formed freshwater tufas. The lowest dcp of the recent freshwater tufas was estimated at Sebesvíz (9.6±1.3%), the highest at Szalajka (16.4±2.4%) and a moderate value at Dobrica Spring (13.8±2.2%). Due to the rapid decrease in atmospheric 14C level we have to compensate the atmospheric 14C drop between the water infiltration time and the deposition time of fresh carbonates to compensate the bomb-effect. The oldest fossil tufa age (BC 6421-6096) was found at Sebesvíz located around 20 metres away from the riverbed, while the youngest fossil tufa ages (a few years/decades old) were found in the recently active area at all sites.